The Australian Welfare State and the Neoliberalism Thesis - Fenna, Alan; Tapper, Alan (Routledge Publishing, Taylor & Francis Group, 2012)
This paper uses Australian Bureau of Statistics fiscal incidence figures to track trends in the Australian welfare state across the period 1984 to 2004. Its general aim is to assess the proposition that recent governments have been ‘grave-diggers’ of the welfare state in Australia. More specifically, it tracks the overall level of social expenditure at the household level and the degree of vertical redistribution between households. Since the period in question covers twelve years of Labor and eight years of Coalition government in Canberra, the authors also seek evidence of political effect in welfare state trends. Their general conclusion is that far from succumbing to neoliberalism, the Australian welfare state became if anything even larger over this period. Neither bipartisan economic liberalisation, nor competing party welfare policies, made much difference to the welfare state when viewed through a fiscal incidence lens.